Preclinical models of congestive heart failure, advantages, and limitations for application in clinical practice - Saura, Marta; Zamorano, Jose Luis; Zaragoza, Carlos (Frontiers in Physiology, 2022)
Congestive heart failure (CHF) has increased greatly over the years for reasons that include recent advances in the treatment of different forms of chronic disease and the aging of the population. Consequently, unlike other cardiac pathologies, neither the pathogenesis of disease nor the therapeutic targets to address this problem have yet been explored to any great extent. Therefore, animal models that produce translational results in patients are valuable assets with which we can address this increasingly common disease. The establishment of an animal model that recapitulates the complexity of the human disease will become a critical element to be addressed, representing a serious challenge given the complexity of the pathogenesis of CHF itself, which will be further compounded by methodological biases that depend on the animal species in use. Thus, models of CHF have been developed in many different species, with different surgical procedures, all with promising results but, for the moment, unable to fully recapitulate the human disease. Large animal models often provide a more promising reality, with all the difficulties that their use entails, and which limit their performance to fewer laboratories, the costly of animal housing, animal handling, specialized facilities, skilled methodological training, and reproducibility as another important limiting factor when considering a valid animal model versus potentially better performing alternatives. In this review we will discuss the different animal models of CHF, their advantages and, above all, the limitations of each procedure with respect to effectiveness of results in terms of clinical application.